2014
DOI: 10.1007/s00167-014-3465-8
|View full text |Cite
|
Sign up to set email alerts
|

Single injection of platelet-rich plasma (PRP) for the treatment of refractory distal biceps tendonitis: long-term results of a prospective multicenter cohort study

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Although recent investigations have demonstrated clinical success with use of US-guided injections for distal bicep tendinopathy [5,6], this article is the first to describe a posterior approach to this area on a live subject, which we believe to be very important for the safe, easy, and effective delivery of the injectate. We believe that a significant risk of injury exists with an anterior approach because of the multiple neurovascular structures in the area and increased difficulty in visualizing the tendon.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although recent investigations have demonstrated clinical success with use of US-guided injections for distal bicep tendinopathy [5,6], this article is the first to describe a posterior approach to this area on a live subject, which we believe to be very important for the safe, easy, and effective delivery of the injectate. We believe that a significant risk of injury exists with an anterior approach because of the multiple neurovascular structures in the area and increased difficulty in visualizing the tendon.…”
Section: Discussionmentioning
confidence: 96%
“…However, one set of investigators [4] noted a 27% percent complication rate, with the most common complications being nerve dysfunction and radioulnar synostosis. Use of platelet-rich plasma (PRP) has been reported as a potential alternative treatment for this condition [5,6]; however, an anterior approach has been used to inject the PRP, which increases the chance of a neurovascular injury.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, two protocols continued NSAID restriction for 6 months after injection. 10,89 47 --------"Strengthening" indicates any activity beyond range of motion and stretching. "Return to play" indicates completion of all physical restrictions.…”
Section: Nsaid Restrictionmentioning
confidence: 99%
“…In a recent multicenter, prospective, cohort study of 12 patients with refractory distal biceps tendinitis who underwent ultrasonographyguided PRP injection, Sanli et al 40 performed the injections with the patients in the supine position and the ultrasonographic probe in orientation with the longitudinal axis of the tendon. They did not report whether the injection was localized in the tendon sheath or in the intrasubstance of the tendon.…”
Section: Distal Biceps Tendonmentioning
confidence: 99%
“…The authors reported improved pain and functional resting and activity outcome scores in all the patients at a mean follow-up of 47 months. 40…”
Section: Distal Biceps Tendonmentioning
confidence: 99%